PEMALSUAN MEREK SEPATU DI INDONESIA: PENGATURAN DAN SANKSI? - Khelvin Risandi; Hari Sutra Disemadi (Jurnal Komunikasi Hukum, 2022)
The laws and regulations in Indonesia have regulated brand counterfeiting, but the cases have not decreased yet. The rise of brand counterfeiting is caused by the condition of society and ineffective laws and regulations. Previous similar studies have discussed the trademark registration procedure and its obstacles as well as the study of mark cancellation, while this research focuses on the regulation and sanctions for brand counterfeiting. The purpose of the study was to find out how the legal arrangements against the perpetrators of counterfeiting shoe brands spread in Indonesia. This study uses a normative juridical research method, with a library search technique. The results of this study indicate the level of effectiveness of laws and regulations related to brands as law enforcement tools in Indonesia, ranging from legal substance to criminal penalty.